Speech Interface Evaluation on Car Navigation System - Many Undesirable Utterances and Sever Noisy Speech - - Obuchi, Yasunari; Nakano, Teppei; Kobayashi, Tetsunori; Hataoka, Nobuo (IntechOpen, 2011)
None